2001
DOI: 10.1074/jbc.m102590200
|View full text |Cite
|
Sign up to set email alerts
|

Anion-mediated Fe3+ Release Mechanism in Ovotransferrin C-lobe

Abstract: The differential properties of anion-mediated Fe 3؉ release between the N-and C-lobes of transferrins have been a focus in transferrin biochemistry. The structural and kinetic characteristics for isolated lobe have, however, been documented with the N-lobe only. Here we demonstrate for the first time the quantitative Fe 3؉ release kinetics and the anion-binding structure for the isolated C-lobe of ovotransferrin. In the presence of pyrophosphate, sulfate, and nitrilotriacetate anions, the C-lobe released Fe 3؉… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 59 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…It was recently reported that the protonation of iron-binding residues of ovotransferrin at acidic pH in the absence of anionic chelators is slow (Abdallah & Chahine, 1999). Studies suggested the release of iron ion from ferric transferrin requires the presence of a simple anion such as pyrophosphate, sulfate, or chloride; however, the rate of anion-mediated iron release is much slower for the C-lobe than for the N-lobe (Mizutani, Muralidhara, et al, 2001;Muralidhara & Hirose, 2000), as there are two anion binding sites in the N-lobe but only one anion-binding site in the C-lobe. Anion binding to the lobe is recognized as the key to iron ion release through multiple mechanisms.…”
Section: Structure Of Ovotransferrinmentioning
confidence: 98%
“…It was recently reported that the protonation of iron-binding residues of ovotransferrin at acidic pH in the absence of anionic chelators is slow (Abdallah & Chahine, 1999). Studies suggested the release of iron ion from ferric transferrin requires the presence of a simple anion such as pyrophosphate, sulfate, or chloride; however, the rate of anion-mediated iron release is much slower for the C-lobe than for the N-lobe (Mizutani, Muralidhara, et al, 2001;Muralidhara & Hirose, 2000), as there are two anion binding sites in the N-lobe but only one anion-binding site in the C-lobe. Anion binding to the lobe is recognized as the key to iron ion release through multiple mechanisms.…”
Section: Structure Of Ovotransferrinmentioning
confidence: 98%
“…The ligand-dependence of k obs was evaluated in terms of a mechanism similar to that in Scheme 4 except that there was no K 1 pathway [59]. We also attempted to fit our data on MDP to this mechanism by including an explicit ligand term in the various reaction steps, but no satisfactory fit was obtained for the combination of saturation and first-order kinetics observed with this ligand.…”
Section: Mechanism Of Iron Releasementioning
confidence: 99%
“…Iron release from the C-terminal site of ovotransferrin at pH 5.6 showed simple saturation kinetics with respect to the concentrations of the ligands NTA, PP i , and sulfate [59]. The ligand-dependence of k obs was evaluated in terms of a mechanism similar to that in Scheme 4 except that there was no K 1 pathway [59].…”
Section: Mechanism Of Iron Releasementioning
confidence: 99%
“…rabbit and porcine, is only 51%. All cellbinding studies (Mason et al, 1987(Mason et al, , 1996Mason & Woodworth, 1984) have utilized ovotransferrin, with the assumption that it is identical to its serum counterpart, but an in vivo irontransport function characteristic of serum transferrin has not been demonstrated for hOT (Mizutani, Muralidhara et al, 2001). The fact that ovotransferrin does not have an irontransport role may, however, be a consequence of its location in egg white.…”
Section: Introductionmentioning
confidence: 99%